Quantum wave packet calculation of reaction probabilities, cross sections, and rate constants for H++LiH ? Li+H2+ reaction - Goegtas, Fahrettin (Wiley, 2006)
The H+ + LiH --> Li + H-2(+) reactive scattering has been studied using a quantum real wave packet method. The state-to-state and state-to-all reaction probabilities for the entitled collision have been calculated at zero total angular momentum. The probabilities for J > 0 are estimated from the J = 0 results by using J-shifting approximation based on the Capture model. The integral cross sections and thermal rate constants are then calculated. (C) 2006 Wiley Periodicals, Inc.
Keywords: reactive scattering; rate constants; reaction cross sections; wave packet study